SMiLE to Life: Meaning in life in healthcare professionals working in palliative care and rehabilitation medicine: SMiLE to Life: Meaning in life in healthcare professionals - Maffoni, Marina; Zanatta, Francesco; Setti, Ilaria; Giorgi, Ines; Velutti, Laura; Giardini, Anna (La Medicina del Lavoro, 2021)
Background: In the healthcare landscape, various protective factors are identified, such as meaning in life (MiL), namely what gives sense to life events. However, little is known about this construct in the healthcare population. Objectives: To describe MiL among healthcare professionals employed in palliative care and neuro-rehabilitation medicine, unveiling possible differences related to medical specialty and socio-demographic characteristics. Methods: In this cross-sectional and multicentre study, palliative care and neuro-rehabilitation professionals were recruited. MiL was evaluated with the Schedule for Meaning in Life Evaluation (SMiLE), which provides a list of meaningful areas, as well as related overall indexes of satisfaction (IoS), weighting (IoW), weighted satisfaction (IoWS). Descriptive statistics, t-test, chi-square, linear and binary logistic regressions were performed. Results: Overall, 297healthcare professionals (palliative care=89, neuro-rehabilitation medicine=208, 47% of participants ≤ 40 years old) completed the evaluation. The sample was intra- and inter-groups heterogeneous, in particular concerning age and professional role. Conversely, no significant group differences emerged in MiL indexes comparisons, nor in the number of MiL listed areas. As for MiL areas, the category “family” increased the IoWS index, while terms related to “finances” contributed to decrease it. Comparing specialties, palliative care professionals were more likely to report areas like “partnership”, “social commitment”, and “satisfaction”. Nurses (n=116), nurse aides (n=47), and therapists (n=67) were more likely to mention health-related terms (e.g. health, physical wellbeing) than physicians and psychologists (n=65). Conclusion: This study highlighted MiL areas among professionals employed in palliative care and neurorehabilitation specialties, providing informative suggestions for tailored health prevention programs which should pay particular attention to social and family relationships, socio-economic status, and health.